Mary Anne saves the day - Martin, Ann M., 1955- (New York : Scholastic, 1987)
When a fight breaks out among the members of the Babysitters Club, timid Mary Anne finds herself becoming more assertive as a baby sitter and in her relationships with her father and friends.
"An Apple paperback.".
4.0
3-6
Keywords: Assertiveness (Psychology) -- Fiction; Babysitters -- Fiction; Friendship -- Fiction; Assertiveness (Psychology) -- Fiction; Babysitters -- Fiction; Friendship -- Fiction